Effects of cold storage duration and 1-MCP treatment on ripening and ‘eating window’ of ‘Hayward’ kiwifruit - Quillehauquy, Victoria (2020)
BACKGROUND:It is known that 1-MCP delays softening in kiwifruit. Time to ripen (eating-window) and its variability are considered useful for planning commercial strategies. However, few studies report the firmness and quality changes during long-term cold storage. OBJECTIVES:To study the effects on ripening and sensory attributes of different 1-MCP treatments during long (180 d) and very long-term (≥210 d) cold storage. Then, the optimal 1-MCP dose was applied to determine the time to ripen after cold storage for 30 to 240 d. METHODS:Kiwifruits were treated with 1-MCP: 0.0 (control), 0.5 and 1.0μL L–1. Maturity indices and sensory analysis were achieved after 180 and 210 d of storage at 0 °C. Ethylene production was also measured. Firmness and number of fruits at eating-ripe state (at 20 °C) were monthly determined after 30 to 240 d of cold storage. RESULTS:1-MCP (1.0μL L–1) delayed kiwifruit softening and prolonged the storage to up 180 d. Longer periods were associated to losses due to over-ripe. Eating windows of 1-MCP-treated fruits were longer than those for untreated fruits. CONCLUSIONS:1.0μL L–1 1-MCP extends the postharvest life of ‘Hayward’ kiwifruit and prolongs the eating window, allowing to plan different commercialization strategies.